Communication Strategy Through Traditional and Weaving Villages to Increase Cultural Promotion in East Sumba - Lestari, Laely Indah; Novianti, Evi; -, Yustikasari (Nyimak: Journal of Communication, 2023)
This study discussed the communication process carried out by the people of East Sumba in an effort increase the promotion of their culture. This study was motivated by the existence of dynamics in cultural development owned by East Sumba, especially related to customs and Ikat Weaving as a cultural heritage in the form of wastra. This study used qualitative research methods with data collection techniques in the form of observation, interviews with six informants spread throughout East Sumba, namely the King of Prailiu Village, Ratu of Praiyawang Rindi Village, Craftsmen from Kambera, Pau, Kanatang and Kaliuda as well as conducting literature studies. The results of the research showed that in the process, communication strategies were carried out in various ways. In terms of the communication strategy carried out by traditional villages, there are efforts to display all the potential that can attract tourists, for example by welcoming tourists using a traditional welcome, developing traditional village areas to be more comfortable, and establishing communication with institutions and individuals. The communication strategy carried out by weaving craftsmen was to cooperate and participate in various events so that Ikat weaving and East Sumba culture in general can be further developed.Keywords: Traditional village, promotion, East Sumba, ikat weaving ABSTRAKPenelitian ini membahas mengenai proses komunikasi yang dilakukan oleh masyarakat Sumba Timur dalam upaya meningkatkan promosi budaya yang dimiliki. Penelitian ini dilatarbelakangi oleh adanya dinamika dalam pengembangan kebudayaan yang dimiliki oleh Sumba Timur, terutama berkaitan dengan adat istiadat serta Tenun Ikat sebagai warisan budaya berupa wastra. Penelitian ini menggunakan metode penelitian kualitatif dengan teknik pengumpulan data berupa observasi, wawancara terhadap enam narasumber yang tersebar di seluruh Sumba Timur, yaitu Raja Kampung Prailiu, Ratu Kampung Praiyawang Rindi, Pengrajin dari Kambera, Pau, Kanatang serta Kaliuda serta melakukan studi literatur. Hasil penelitian menunjukkan bahwa dalam prosesnya, strategi komunikasi dilakukan dengan berbagai cara. Dalam segi strategi komunikasi yang dilakukan oleh kampung adat, terdapat upaya untuk menampilkan seluruh potensi yang dapat menarik wisatawan misalnya dengan menyambut wisatawan menggunakan penyambutan adat, mengembangkan kawasan kampung adat menjadi lebih nyaman, serta menjalin komunikasi dengan lembaga maupun individu. Adapun strategi komunikasi yang dilakukan oleh pengrajin tenun ialah dengan melakukan kerjasama serta mengikuti berbagai event agar tenun ikat dan budaya Sumba Timur secara umum dapat lebih berkembang.Kata Kunci: Kampung adat, promosi, Sumba Timur, tenun ikat